UPLC-MS/MS profiling, antioxidant and anti-inflammatory activities, and potential health benefits prediction of phenolic compounds in hazel leaf - Zhao, Jiarui; Wang, Xinhe; Wang, Yuchen; Lv, Guangfu; Lin, He; Lin, Zhe (Frontiers in Nutrition, 2023)
In the present study, the profile of free, conjugated and bound phenolic compounds from hazel leaf was detected and their antioxidant and anti-inflammatory activities were investigated. The potential health benefits of different phenolic compounds were also predicted. The results showed that the 35 phenolic substances of free, conjugated and bound forms were identified including phenolic acids, flavonoids and catechins. Most of the hazel leaf phenolics were presented in free form, followed by conjugated and bound form. All the fractions effectively inhibited the production of reactive oxygen species and malondialdehyde in TBHP-stimulated human umbilical vein endothelial cells by enhancing endogenous superoxide dismutase, and accordingly alleviated inflammatory cytokines (NO, IL-1β, TNF-α and IL-6) in LPS-stimulated RAW264.7 cells, showing obvious antioxidant and anti-inflammatory capacity. Moreover, combined with network pharmacology, the potential therapeutic effects and functional pathways of hazel leaf phenolics were predicted, which provided value basis for exploring their treatment on diseases and developing health products in the future.